A database as a tool for analysis and prevention of hydrogeological instability events in an urban area: an example in the Naples area (Italy) - Alberico, Ines; Ramondini, Massimo; Zito, Giancarlo (Italian journal of engineering geology and environment, 2006)
A methodological approach for the assessment of hydrogeolog- ical instability events (HIEs) in the Napoli municipality area is proposed. The statistical analysis of collected data (about 900 drill holes, 600 Cone Penetration Test (CPT), climatic data and about 4500 HIEs) has shown: a) an increase in hollow and sinking (HS), deep hollow and deep sinking (DHS) as well as instability events concerning supporting wall (IEW) limited over short time, in case of intense but short rainfall; b) an increase of HS and DHS extended in time, in case of intense and protracted rainfall. The wide spatial distribution of the Anthropic Reworked Material, in the first 5 meters depth, reduced the effects of the other deposits and of their mechanical features (the mean CPT profiles show a quite variable resistance value qc) on the occurrence of the HIEs. The HS and DHS (about 62% of total instability events) occur in areas characterized by the presence of drain-sewer net and pluvial net that carry the water volume produced during intense and protracted rainfall, while the IEW (representing about 10% of total instability events) occurs mainly in areas characterized by unwelded pyroclastic deposits and medium-high slopes.